A mixed-mode model for the ferrite-to-austenite transformation in a ferrite/pearlite microstructure. (15th April 2015) - Mecozzi, M.G.; Bos, C.; Sietsma, J.
Abstract: A concise semi-analytical mixed-mode model is proposed to describe the ferrite-to-austenite transformation kinetics. The initial microstructure for the model consists of a ferrite matrix with supersaturated austenite grains. The carbon supersaturation of austenite grains resulted from the rapid dissolution of pearlite colonies present in the initial microstructure. A similar approach to the one used for describing the ferrite growth kinetics (Bos and Sietsma, 2007) was used, employing a sharp interface between the phases. In comparison to ferrite growth, the carbon concentration profile of the growing austenite contains an additional parameter, which is the carbon concentration at the centre of the grain. This extra parameter is accounted for by assuming a parabolic carbon profile in the austenite. A comparison with a numerical solution of the differential equations shows that the developed semi-analytical mixed-mode model gives a good description of the ferrite-to-austenite transformation, significantly more accurate over the entire course of the transformation than the classical interface-controlled and diffusion-controlled models. Significant deviations from the numerical solution, as a result of the parabolic approximation, are limited to the initial stage of the transformation.